Distributive shock, cardiac arrhythmias and multiple organ failure following surgery of a fourth ventricular epidermoid. (31st March 2016) - Bercker, Sven; Meixensberger, Jürgen; Laudi, Sven; Renner, Christof
Abstract : A 33-years-old male patient presented with cardiac arrhythmias, acute shock and multiple organ dysfunction after the surgical removal of a massive epidermoid posterior to the brainstem. The patient initially presented with paraesthesia along the right C6 dermatome due to a big tumour at the brain stem. Surgical removal was performed without adverse events and he was transferred to our intensive care unit (ICU) immediately after the operation. Though initially showing a stable postsurgical course he developed cardiac arrhythmias and a state of acute distributive shock with consecutive multi organ failure. Extensive diagnostic measures could not identify a specific cause for this rapid deterioration. However, under carefully monitored symptomatic therapy the patient improved quickly, was extubated 72 h after admission and discharged from the ICU 6 days later. The follow-up did not show any persisting neurological deficits and no evidence of a residual tumour in the MRI-study.